Hard X-ray photoemission study of the Fabre salts (TMTTF)(2)X (X = SbF6 and PF6) - Medjanik, Katerina; Souza, Mariano de [UNESP]; Kutnyakhov, Dmytro; Gloskovskii, Andrei; Mueller, Jens; Lang, Michael; Pouget, Jean-Paul; Foury-Leylekian, Pascale; Moradpour, Alec; Elmers, Hans-Joachim; Schoenhense, Gerd (Springer, 2014)
Core-level photoemission spectra of the Fabre salts with X = SbF6 and PF6 were taken using hard X-rays from PETRA III, Hamburg. In these salts TMTTF layers show a significant stack dimerization with a charge transfer of 1e per dimer to the anion SbF6 or PF6. At room temperature and slightly below the core-level spectra exhibit single lines, characteristic for a well-screened metallic state. At reduced temperatures progressive charge localization sets in, followed by a 2nd order phase transition into a charge-ordered ground state. In both salts groups of new core-level signals occur, shifted towards lower kinetic energies. This is indicative of a reduced transverse-conductivity across the anion layers, visible as layer-dependent charge depletion for both samples. The surface potential was traced via shifts of core-level signals of an adsorbate. A well-defined potential could be established by a conducting cap layer of 5 nm aluminum which appears "transparent" due to the large probing depth of HAXPES (8-10 nm). At the transition into the charge-ordered phase the fluorine 1s line of (TMTTF)(2)SbF6 shifts by 2.8 eV to higher binding energy. This is a spectroscopic fingerprint of the loss of inversion symmetry accompanied by a cooperative shift of the SbF6 anions towards the more positively charged TMTTF donors. This shift does not occur for the X = PF6 compound, most likely due to smaller charge disproportion or due to the presence of charge disorder.